Flood vulnerability under sea level rise for a coastal community located in a backbarrier environment - Croteau, Raphaelle (2022)
Sea level rise and other hydro-meteorological hazards will be the biggest threat to coastal communities within this century. In addition, coasts of the world have been highly modified to accommodate humans, which has caused numerous problems such as coastal erosion, pollution, and destruction of natural environments. Floods represent some of the most serious hazards on coastal areas. Their impact will most probably increase in the future due to both sea level rise and increased human occupation. The main objective of this study was to evaluate the potential ocean-driven inundation in a small village (Culatra, Portugal) located in a backbarrier environment, including the impacts of a recently built harbor and of sea level rise. The shoreline evolution was measured with the digital shoreline analysis system for a period of ~10 years before and after the harbor construction. Then, a flood analysis was performed using a new GIS based methodology to measure the inundation extension using total water levels (tides + storm surge + sea level rise) and an associated inundation extension. Finally, the post-harbor retreating trends were incorporated in the flood analysis to determine the influence of the harbor in the inundation extension. The results show that the shoreline changes related to the harbor construction are concentrated around the harbor, while the rest of the study area is stabilizing. The new inundation extension methodology shows that the village is somewhat protected for current and 2050 scenarios of total water levels of a 1-year return period but would be affected by 100-year return periods, especially in 2050. The shoreline retreat induced by the harbor shows minimal impacts in the flooding extension compared to the increase in water level. To prevent flooding in the next 30 years, simple measures like elevating dunes, nourishing key sectors, and protecting marsh vegetation can be very effective. For 2100, both scenarios (1-year and 100-year return periods) show a highly impacted village that will require strong adaptation measures in order to remain in the area after 2050 since all the main infrastructures would be flooded on a yearly basis.